1995
DOI: 10.1161/01.cir.91.7.1952
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Increased Estrogen Status and Increased Fibrinolytic Potential in the Framingham Offspring Study

Abstract: Each of these comparisons indicates that the cardioprotective effect of estrogen may be mediated, in part, by an increase in fibrinolytic potential. These findings might provide at least a partial explanation for the protection against cardiovascular disease experienced by premenopausal women, and the loss of that protection following menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
126
1
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(156 citation statements)
references
References 48 publications
22
126
1
7
Order By: Relevance
“…Thus, increased accumulation of PAI-1 was observed in media of cultured aortic rings from cp/cp males even without addition of exogenous insulin. The lack of increased expression of PAI-1 by aortic rings from corpulent females is consistent with decreased vascular elaboration of PAI-1 in direct proportion to the circulating concentration of oestrogen, as reported in the Framingham Offspring Study [35].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, increased accumulation of PAI-1 was observed in media of cultured aortic rings from cp/cp males even without addition of exogenous insulin. The lack of increased expression of PAI-1 by aortic rings from corpulent females is consistent with decreased vascular elaboration of PAI-1 in direct proportion to the circulating concentration of oestrogen, as reported in the Framingham Offspring Study [35].…”
Section: Discussionsupporting
confidence: 85%
“…Reduced PAI-1 levels and higher t-PA levels after HRT have been reported, which can increase the fibrinolytic potential in these patients. [46][47][48] These results confirm that oral CEE plus MP can reduce AT-III levels, as we observed previously, whereas unopposed CEE or transdermal 17beta-estradiol associated with MP did not change AT-III levels. There is no evidence of activation of blood coagulation, since the AT-III level was not reduced below normal range, and the F1+2 elevation was only modest.…”
Section: Group C At-iii (%)supporting
confidence: 90%
“…However, one explanation has been proposed, in which differences in biology and physiology between the genders result in gender differences in the pathogeny, therapeutic effects and prognosis of CVD [40][41][42][43] . During menopause, women are at higher risk of cardiovascular disease due to the loss of the vascular protective effects of estrogen, which helps to prevent myocardial and vascular diseases 44,45) . In addition, Madonna M. Roche reported that CVD affects women with diabetes more significantly than men, especially when the disease is diagnosed at a later stage 46) .…”
Section: Discussionmentioning
confidence: 99%